Evaluation of the Kurikulum Merdeka in dance learning for junior high schools - Nadia Putri Kharismawati; Zainal Arifin (Himpunan Pengembang Kurikulum Indonesia, 2024)
Curriculum evaluation is a crucial component in the educational process that assesses the effectiveness of curriculum implementation and identifies strengths and weaknesses in its planning and application. Curriculum evaluation plays a crucial role in ensuring the successful implementation of the Kurikulum Merdeka, particularly in dance education, by assessing the effectiveness of planning, implementation, and learning outcomes. This study aims to evaluate the implementation of the Kurikulum Merdeka based on its relevance to the curriculum's achievements, covering the aspects of planning, implementation, and assessment of dance education. The study employs a descriptive method with a qualitative approach, collecting data through observation, interviews, and documentation from SMPN 1 Cimalaka. Participants in this research include the school principal, the vice principal of curriculum, art and culture teachers, and seventh-grade students. The study results indicate that the dance education planning at SMPN 1 Cimalaka aligns with the guidelines of the Kurikulum Merdeka. In practice, teachers have successfully adapted teaching methods to meet students' needs, though there are differences between the methods recommended in the modules and classroom practices. The evaluation of learning is systematically conducted using formative and summative assessments to measure student achievement. Abstrak Evaluasi kurikulum merupakan komponen penting dalam proses pendidikan yang berfungsi untuk menilai efektivitas pelaksanaan kurikulum serta mengidentifikasi kekuatan dan kelemahan dalam perencanaan dan penerapannya. Evaluasi kurikulum berperan penting dalam memastikan keberhasilan penerapan Kurikulum Merdeka, terutama dalam pembelajaran seni tari, dengan cara menilai efektivitas perencanaan, pelaksanaan, dan pencapaian hasil belajar. Penelitian ini bertujuan untuk mengevaluasi pelaksanaan kurikulum merdeka, berdasarkan relevansinya dalam capaian kurikulum, dengan meliputi aspek perencanaan, pelaksanaan dan penilaian pembelajaran tari. Studi ini menggunakan metode deskriptif dengan pendekatan kualitatif, di mana data dikumpulkan melalui observasi, wawancara, dan dokumentasi dari SMPN 1 Cimalaka. Partisipan dalam penelitian ini meliputi kepala sekolah, wakil kepala sekolah bidang kurikulum, guru seni budaya, dan siswa kelas VII. Hasil penelitian menunjukkan bahwa perencanaan pembelajaran tari di SMPN 1 Cimalaka telah sesuai dengan panduan Kurikulum Merdeka. Dalam pelaksanaannya, guru berhasil mengadaptasi metode pengajaran sesuai kebutuhan siswa, meskipun ada perbedaan antara metode yang direkomendasikan modul dan praktik di kelas. Evaluasi pembelajaran dilakukan secara sistematis dengan menggunakan asesmen formatif dan sumatif untuk mengukur pencapaian siswa. Kata Kunci: evaluasi kurikulum; pendidikan seni tari; kurikulum merdeka